Analysis of Regional Original Revenue (PAD) to Evaluate The Financial Performance of Regional Government of DKI Jakarta Province for The Financial Years 2019 – 2023 - Monica Dwianita Febrianti; Sony Devano (Indonesian Journal of Economics, Social, and Humanities, 2026)
This study aims to analyze the financial performance of the DKI Jakarta Provincial Government for the Financial Years 2019-2023, especially in the management of PAD using financial ratios. The research method used is qualitative-descriptive using primary data from interview results and secondary data from Financial Statements. The results of this study show that the financial performance of DKI Jakarta Province has been competent and independent in managing regional autonomy affairs. The performance of the Jakarta Provincial Government in exceeding the budgeted PAD target is relatively good, although it is still not optimal in realizing all potential sources of PAD revenue. Meanwhile, the financial capabilities of the Jakarta Provincial Government show that regional conditions are ideal and relatively high, which indicates that the Jakarta Provincial Government has good regional financial capabilities in managing available financial resources and is ready to welcome the era of regional autonomy. In addition, the results of forecasting through the trend moment method also show that regional original revenue will continue to increase every year in the next five years, which indicates that DKI Jakarta Province in the next five years has great potential to increase regional original revenue.